Peningkatan Partisipasi Masyarakat dalam Kegiatan Keagamaan di Desa Pardomuan Kabupaten Mandailing Natal - Farid, Ahmad Salman (Jurnal Pengabdian Harapan Bangsa, 2023)
This activity aims to enhance community participation in religious activities in the village of Pardomuan, Mandailing Natal Regency, through the implementation of the Service Learning method. Pardomuan Village was chosen as the location due to its perceived potential for the development of religious activities, yet the level of community participation needs improvement. The Service Learning method was selected as the primary approach in this community service because it can integrate learning and service to the community, providing dual benefits. The community service team, comprising students, lecturers, and Islamic religious instructors, collaborated with the residents of Pardomuan Village to design and execute various religious activities. The initial steps involved mapping the community's needs through surveys and group discussions. Subsequently, the team designed religious programs involving various segments of the population, including children, teenagers, adults, and the elderly. These activities encompassed religious lectures, religious skill training, and socio-religious activities to enhance a sense of community. The outcomes of this community service are evident in the increased community participation in religious activities, improved understanding of religious matters, and the formation of a solidarity network among the residents of Pardomuan Village. Thus, it is expected that the Service Learning method can serve as an effective model in addressing the challenges of community participation in religious activities, particularly in a rural context.